Meta-frontier efficiency analysis of real estate and construction firms in Indonesia. Issue 10 (3rd October 2022) - Hoang, Viet-Ngu; Raharjo, Joko Purnomo; Susilawati, Connie
Abstract: Improving the productive efficiency (also called technical efficiency) of real estate and construction firms (RECFs) is essential to tackle the sustained shortage of housing supply and the increasing unaffordability of housing in developing countries. However, there are few studies that focus on this issue in the context of developing countries; and available literature focuses mainly on firms listed on stock markets. Our study employs the meta-frontier framework to measure the efficiency of 832 small, medium, and large RECFs across Indonesia from 2012 to 2016, using a data envelopment analysis technique. The meta-frontier framework allows for different production technologies and different business environments operated by firms of different sizes. Under the specification of group-specific production frontiers, large firms obtain the highest average efficiency scores (0.694), followed by medium firms (0.529), and small firms (0.479). The technology gaps between the meta-frontier and the group-frontiers for small and medium firms are relatively large, suggesting that the overall industry would be able to achieve remarkable efficiency improvement if firms could access technologies used by more efficient firms. Our results also show that determinants of the efficiency vary across firm groups, suggesting that policy and managerial interventions tailored to each group would have more impact on the overall productive efficiency of the entire industry.